Thio- and selenosemicarbazones as antiprotozoal agents against Trypanosoma cruzi and Trichomonas vaginalis - Alexandra Ibáñez-Escribano; Cristina Fonseca-Berzal; Mónica Martínez-Montiel; Manuel Álvarez-Márquez; María Gómez-Núñez; Manuel Lacueva-Arnedo; Teresa Espinosa-Buitrago; Tania Martín-Pérez; José Antonio Escario; Penélope Merino-Montiel; Sara Montiel-Smith; Alicia Gómez-Barrio; et al. (Taylor & Francis Group, 2022)
Herein, we report the preparation of a panel of Schiff bases analogues as antiprotozoal agents by modification of the stereoelectronic effects of the substituents on N-1 and N-4 and the nature of the chalcogen atom (S, Se). These compounds were evaluated towards Trypanosoma cruzi and Trichomonas vaginalis. Thiosemicarbazide 31 showed the best trypanocidal profile (epimastigotes), similar to benznidazole (BZ): IC50 (31)=28.72 μM (CL-B5 strain) and 33.65 μM (Y strain), IC50 (BZ)=25.31 μM (CL-B5) and 22.73 μM (Y); it lacked toxicity over mammalian cells (CC50 > 256 µM). Thiosemicarbazones 49, 51 and 63 showed remarkable trichomonacidal effects (IC50 =16.39, 14.84 and 14.89 µM) and no unspecific cytotoxicity towards Vero cells (CC50 ≥ 275 µM). Selenoisosters 74 and 75 presented a slightly enhanced activity (IC50=11.10 and 11.02 µM, respectively). Hydrogenosome membrane potential and structural changes were analysed to get more insight into the trichomonacidal mechanism.